Liquidity Risk – Measurement and Control - Naďa Blahová (European Financial and Accounting Journal, 2012)
The article deals with the liquidity risk in the banks in the context of the financial crisis. At first, the balance sheet and market liquidity are defined and the main principles of the methods for measuring liquidity risk, which banks use, are identified. Then follow review of main challenges of managing the liquidity of banks. Finally, it discusses qualitative regulatory requirements and eligibility of newly formulated standards with regard to minimum liquidity in general and in relation to the Czech banking sector in particular.
Keywords: G21; G28; 650; Risk; Regulation; Liquidity; Financial market; Bank